Expressive Illocution Speech on Denny Sumargo's Podcast - Maini, Tiur; Hermawan, Hermawan (Civiliza Publishing, Indonesia., 2025)
Language is an important tool in communication that allows humans to convey feelings, thoughts, and attitudes, including through expressive speech acts. In the realm of pragmatics, expressive speech acts reflect the speaker's psychological attitude towards a particular situation. This study aims to analyze the form and function of expressive illocutionary speech acts in the podcast Curhat Bang Denny Sumargo episode with Thariq Halilintar and Aliyah Massaid which aired on August 23, 2024. This study uses a qualitative descriptive method with a listening and note-taking technique to identify speech containing elements of expressive speech acts based on Leech's theory (1993), which includes six types: saying thank you, saying congratulations, apologizing, criticizing, praising, and expressing condolences. The results of the study showed that there were 54 expressive speech act data spread across the categories: praising 23 data, apologizing 11 data, criticizing 9 data, saying thank you 8 data, saying congratulations 2 data, and expressing condolences 1 data. The expressive speech act of praising is the most dominant form, which shows the tendency of speakers to build positive relationships and maintain politeness in interactions. These findings show that podcasts as a digital communication medium are not only a means of sharing information, but also a space for complex emotional and psychological expression. This study broadens the understanding of language use in the context of social media and opens up opportunities for further exploration in